Functional Features of Footnotes in Literary Translation - Фролова, Ірина Євгенівна; Углєвата, Аліна Миколаївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2021)
The article provides a functional analysis of footnotes in literary translation. A literary text, besides the textual, comprises metatextual, intertextual and, possibly, paratextual elements. The paratextual elements can be also introduced while rendering a literary text in another language, in this case they can be added by translator or editor. Paratext comprises a number of components, footnotes among them, namely, the documentary ones which are subjected to analysis in this article. Concentrating upon the functional features of footnotes, we argue that they are rooted in their formal and semantic-cognitive characteristics. The formal – graphic – features of the footnotes under study are as follows: they are always placed at the foot of a page below a line, marked mostly by a figure (in some cases by an asterisk), printed in small font (sometimes in italic font). All these perform the attractive function, drawing the reader's attention to the footnote. The semantic-cognitive features of footnotes come in two basic varieties and one minor one. The footnotes of the two basic groups provide information about a textual element, that of universal or culturally or lingvoculturally specific character thus performing the explanatory function. The footnotes of the third - minor - group provide information about an intertextual element, in particular, about the authorship of the translation of this element. Thus they perform the additive function.